Acute Asthma Management in a Tertiary Hospital in Oman - Suhaila Al Farsi; Nasser Al Busaidi (Oman Medical Journal)
Objectives: The quality of asthma management in tertiary hospitals’ emergency departments (EDs) is key to sustained asthma control. We assessed the quality of asthma care and adherence to guidelines at the Royal Hospital in Oman. Methods: We conducted a retrospective, observational study examining the medical records of asthma patients who presented to the ED between 1 June 2014 and 1 June 2016. Results: A total of 217 patients were included in the study. Lack of proper documentation was observed throughout the study. Only 80 patients (59.7% of 134 available records) were on controller therapy and 51 were reported to be compliant. No asthma severity assessment was conducted, and 57 (32.9%) patients experienced respiratory distress. Peak expiratory flow rate measurements were not performed for all patients; chest X-ray was performed for 145 (66.8%) patients, and blood gas analysis for 83 (38.2%). The mean±SD time from the initial assessment to the treatment initiation was 12.0±11.0 minutes. Systemic steroids and nebulizers were used for initial management in 70.5% (n = 153) and 96.3% (n = 209) of patients, respectively. Reassessments at one and two hours following initial assessment were not done for all patients; reassessment records were missing for 50 (54.9%) patients after the first hour, and 50 patients after the second hour. Out of the total sample, 45 (20.7%) patients required hospital admission, with the majority (93.3%) admitted to the medical ward. Post-discharge procedures recommended by guidelines were rarely employed. Conclusions: There is a serious lack of adherence to asthma management guidelines in the ED. The 2009 Omani Ministry of Health guidelines should be updated, considering the recent updates of Global Initiative for Asthma strategies, adopted as the standard of care, and disseminated with regular monitoring to ensure compliance.